Getting the Words Right: When Wording of Job Ads Affects Ethnic Minorities' Application Decisions. (November 2017) - Wille, Lien; Derous, Eva
Targeted recruitment strategies aim to communicate job vacancies to specific groups of job seekers that organizations wish to attract, such as qualified ethnic minorities. Typically, these strategies do not consider how person requirements are communicated in job advertisements and how job seekers from different ethnic groups react to such requirements. Two field experiments among actual job seekers investigated whether the type of required trait and the wording of traits affected ethnic minorities' job attraction (Study 1, N = 140) and qualified ethnic minorities' and majorities' decision to apply (Study 2, N = 130). Findings show that ethnic minority job seekers were less attracted to job ads targeting a trait they have negative meta-stereotypes about. Wording of traits did not moderate this effect. However, ethnic minority job seekers who were qualified for a negatively meta-stereotyped trait decided not to apply when that trait was worded in a dispositional (vs. a behavioral) way.